(untitled) (Revista Iberoamericana de Bioética, 2023)
This research analyses conflicts in the field of global bioethics, in a dialogue with integral ecology, related to mineral neo-extractivism in Latin America, focusing on the corporate socio-environmental crime committed by Vale S/A, in Brumadinho in the Brazilian state of Minas Gerais. In order to achieve this objective, it takes as its starting point the theoretical proposal of Critical Bioethics, incorporating reflections on the Anthropocene, especially the Mineralocene. The characterisation of the Brumadinho crime, as well as the interdisciplinary amalgamation with integral ecology, helps to understand the bioethical conflicts related to corporate socio-environmental crimes, allowing us to identify the “nebulous” governance of mineral neo-extractivism, as well as indicating “counter-nebulae” of resistance in the bodies and territories of the subjects who suffer the damage of global bioethical conflicts.